STUDI KUALITATIF PRAKTIK PEMBERIAN MAKAN BAYI USIA 0-2 TAHUN OLEH IBU YANG MENIKAH DINI DI KABUPATEN TABANAN BALI TAHUN 2020 - Narta Santi, Luh Erlanggita; Lubis, Dinar Saurmauli; Kurniati, Desak Putu Yuli (ARCHIVE OF COMMUNITY HEALTH; Vol 9 No 3 (2022): Desember 2022, 2022)
ABSTRACT Baduta nutritional status is often associated with breastfeeding and complementary feeding practices. Young mother tended to stop breastfeeding earlier than mothers whose ages were mature. The research aims to explore the practice of feeding to baduta by young mother in Tabanan district. This study used a qualitative approach by conducting interviews with 5 mothers who were married early at the age of 19 years and under along with the mother's family of 5 supporting informants. The data analysis used thematic analysis, namely identifying the themes of the interview transcripts and the results of observations as well as deductively using planned behavior theory. Data triangulation was carried out by sources and methods. The results of this study are all research informants who do not perform IMD, exclusive breastfeeding, and provide early complementary foods. Mothers not knowing about breastfeeding techniques tended to stop breastfeeding. There is a perception of insufficient breastfeeding which results in early complementary feeding. The failure of breastfeeding is due to lack of information from health workers and encouragement from families in providing early complementary foods. The conclusion in this study is that there are obstacles and support in feeding baduta by young mothers. Apart from the perceptions of mothers, families and health workers also play a role in feeding baduta. Key word : Young mother, Barriers, Support